Biologics in rheumatic diseases - Abdullah, Hilmi (2017)
This talk was about the use of biological therapies such as Tumour Necrosis Factor Inhibitor in the treatment of inflammatory arthritides such as Rheumatoid Arthritis, psoriatic arthritis and ankylosing spondylitis